What triggers firms to appoint outside directors beyond the legal minimum requirement? - Bum-Jin Park (South African Journal of Business Management, 2018)
Background: Although previous studies provide important insights on how firms respond to institutional pressure, they fail to acknowledge the salience of globalisation that results in institutional pressures diffusing across countries.Objectives: Drawing on a selective adaptation model, this article examines whether firms comply with reforms to board structures beyond the minimum legal requirement.Method: It investigates the determinants of appointing outside directors beyond the minimum legal requirement by analysing the relationship between four main variables and minimum compliance.Results: Using a sample of Korean listed firms during 2002–2014, this study found that the salient organisational conditions (firm complexity and firm performance) and key organisational actors (controlling shareholders and foreign investors) determine the extent to which firms appoint outside directors on their boards.Conclusion: This study contributes to the strategy literature that examines organisational response to institutional pressure, furthering the understanding of why there is heterogeneity in firm decisions even from firms in the same institutional environment that face similar institutional pressures. Moreover, it makes a contribution to corporate governance literature, in particular to the adoption of governance mechanisms that originate from foreign models.
Keywords: 650